Posted by **Greg** on Thursday, June 9, 2011 at 1:03am.

Can someone show how to this question.

Loga(x+3) + Loga(x-3) = 3

I don't know if I'm typing this correctly the a is the base.

So, I'm thinking,

Loga((x+3)(x-3)) = 3

(x+3)(x-3) = 3^a

x^2 - 9 = 3^a,

x^2 = 3^a + 9

x = sqrt(3^a + 9)

but now I'm stuck, I don't know how to proceed. I don't know if this is the answer...

## Answer this Question

## Related Questions

- math/calculus - solve the equation loga(x-5)- loga (x+9)=loga(x-7)-loga(x+9) all...
- Algebra help - If loga 8=2.079, loga 5=1.609, and loga 3=1.099, find the ...
- Math Algebra 2 - #4. Express the logarithm in terms of log2M and log2N: log2 1/...
- math-please help,need quickly - loga(x-5)-loga(x+9)=loga(x-7)-loga(x+9) all the ...
- math trouble - I have 2 problems I need help with using either substitution or ...
- Math Algebra 2 - How do I put log in a TI-84 calculator. #1.Express the ...
- HELP! - I have no idea what the answer to this problem is, I'm given choices but...
- Math - Solve the logarithmic equation. Please show all of your work. Loga(x+4...
- Math - Which of the following is not a property of logarithms? A. log(A - B) = ...
- algebra - express as an equivalant expression that is a single logarithmic and ...